HIV infection, aging, and immune function: implications for cancer risk and prevention. - Dubrow, Robert; Silverberg, Michael J; Park, Lesley S; Crothers, Kristina; Justice, Amy C (Current opinion in oncology, 2012)
Combination antiretroviral therapy (ART) has turned HIV infection into a complex chronic disease. This article documents cancer risk among HIV-infected persons, reviews immune system effects of HIV infection in relation to cancer risk, discusses implications for cancer prevention, and suggests future research directions.
Keywords: Age Factors; HIV Infections; Humans; Neoplasms